Oral Tradition as Cultural Pedagogy: Preserving Kotah Pehapeng Waha Pledang in The Lifelong Learning Practices of Lamakera - karim, syakban abdul (Universitas Islam Negeri (UIN) Mataram, 2025)
The Kotah Pehapeng–Waha Pledang oral tradition of Lamakera, East Flores, represents an intangible cultural heritage that embodies educational, moral, spiritual, and collective identity values. This study adopts a qualitative approach using literature review and a phenomenological-hermeneutic paradigm. The findings indicate that despite shifts in communication patterns and generational preferences toward digital media, the Lamakera community continues to demonstrate cultural resilience through adaptive innovation. Digital documentation, curricular integration, and active participation by community and cultural institutions are identified as key strategies for preserving the tradition. Far from being a static relic, the oral tradition acts as a medium for social identity reconstruction and value transmission within a rapidly globalizing context. This research highlights the importance of sustained preservation efforts through synergizing traditional practices with digital platforms to ensure the continued relevance of oral heritage in shaping culturally rooted and ethically grounded communities.